Development of a Mini-CEX tool in simulation and evaluation of the subcutaneous drug administration skills of senior nursing students before graduation: A Pilot Study - Uzelli Yilmaz, Derya; Akin Palandoken, Esra; Hamarat Tuncali, Sevil; Caliskan, Sinem (Annals of Medical Research, 2021)
Aim: This study was conducted in order to development of a Mini-CEX tool based on the core competencies of nurses and evaluation of the subcutaneous drug administration skills of senior nursing students before graduation. Materials and Methods: A Mini-CEX tool was developed based on the core competencies of nurses. When opinion of the expert’s evaluation was confirmed, the students’ clinical competencies of the subcutaneous drug administration skills were evaluated simultaneously in standardized patient simulation with the Mini-CEX form (n=66). Results: The mean score for the whole mini-CEX was 6.13 ± 1.20 (range = 1‑9). The results of this research indicate the feasibility of using our Mini-CEX tool. The mean student satisfaction score was high at 4.59 ± 0.46 (range = 1‑5). 69.7% (n=46) of students thought that feedback is an important their professional development and 62.1% (n=41) of students thought that mini-CEX are an important educational tool. Conclusion: The results of this research indicate the feasibility of using our Mini-CEX tool. The study supports of the use of the Mini-CEX to assess clinical competence through simulation. The study recommends the use of applications that increase the level of realism such as the use of standardized patients or moulages in examinations which aim to simultaneously evaluate student skills such as communication and decision making.
Keywords: Mini-CEX; moulage; nursing competence; nursing education; simulation; standardized patient